Religious, ethical and legal considerations in end-of life issues: fundamental requisites for medical decision-making - Jahn Kassim, Puteri Nemie; Alias, Fadhlina (2014)
Religion and spirituality has undoubtedly played a major and intervening role in a person’s life and health matters. The growth of patient autonomy and the right of self-determination have also made patient’s religious affiliation a key component in medical decision-making. This is particularly pertinent in issues involving end of life choices such as withdrawing and withholding life support, medical treatment, nutritional feeding and do-not resuscitate orders. Further, end of life issues affect not only the patient’s values and beliefs but also family members and the medical profession. The law has also played an intervening role in resolving the conflicts between sanctity of life and quality of life in issues involving end of life decisions. The medical profession in dealing with the inherent ethical and legal dilemmas need to be sensitive not only in patients’ varying religious beliefs and cultural values but to the developing legal and ethical standards as well. There is a need for the medical profession to be guided on the ethical obligations, legal demands and religious expectations prior to handling difficult end of life decisions. The development of comprehensive ethical codes in congruent with developing legal standards may offer clear guidance to the medical profession in making sound medical decisions.